China's rise in africa : perspectives on a developing connection - Kopinski, Dominik; Polus, Andrzej; Taylor, Ian. ([S.l.] : Routledge, 2011)
In seeking to cultivate external relations with African countries, China has long stressed its commonly shared roots with African nations as a developing country rather than a Western state, and as such the symbolic attraction of China clearly reverberates with many African elites who seem to look on China as a positive development model. However, it should be noted that this has not been embraced solely by dictatorial or authoritarian regimes but in fact China$1 (Bs approach to non-interference has struck a chord even with those democratically elected leaders in Africa. While such practices clearly benefit African elites, it is remains doubtful that they do so for ordinary Africans, although sustained analysis suggests that potential exists, albeit hampered by the modalities of governance on the continent. This book brings together experts on the topic to throw light on some of the more contentious aspects of the relationship. This book was published as a special issue of the Journal of Contemporary African Studies .s
Keywords: Africa; China; Economic development; International relations